Analisis Implementasi Total Quality Management (TQM) Pada Kasus Pending Klaim Jaminan Kesehatan Nasional (JKN) Di RSUD Kendal Tahun 2018 - Faik Agiwahyuanto; Shinta Octaviasuni; Moh. Umar Nauful Fajri (Jurnal Manajemen Kesehatan Indonesia, 2019)
Background: Improvements in hospitals are needed to become a going concern hospital. One strategy that can be applied is Total Quality Management (TQM). TQM seeks continuous improvement of all hospital functions. The National Health Insurance Program (JKN) has been run by the Regional Hospital General Hospital (RSUD) Dr. H. Soewondo Kendal as of January 1st, 2014. Health financing is the most important part of implementing JKN held in hospitals by BPJS Kesehatan through submission of claims. During the implementation of JKN in Kendal General Hospital, problems were found between the difference between the visits of BPJS Health patients to hospitalizations and the Health BPJS visits claimed, thus causing pending cases of late claims. File claims that are late in submission will be included in the claim process the following month.Objective: Analyze the pending causes of the Health BPJS file based on TQM implementation.Method: This type of research uses qualitative phenomenological methods and case study research designs. The research subjects were 7 officers who were directly involved in the claim process. The research instrument is the patient claim file by paying BPJS Kesehatan. Data analysis using the Importance Performance Analysis (IPA) technique.Summary: Pending causes of claims from casemix manpower factors with educational background not medical records and lack of coding staff. The factor of the casemix section method is no Standard Operating Procedure (SOP) for claiming BPJS Health. Material factors still have claims files that cannot be submitted due to inappropriate SEP numbers or often purif. Casemix machine factors (INA CBGs) already use computers and printers. The money factor for hospital income was delayed due to pending claims and claims that failed to purify.Conclusion: The process of implementing the BPJS Health claim in Dr. Hospital H. Soewondo Kendal is in accordance with the theory but there are still file claims that are pending.Suggestion: Organize education to officers intensively and standardize the time of collecting investigations and operating reports to medical records so that the files will be claimed as soon as possible and sent to BPJS.